Spatiotemporal Trends in the Incidence of Gastrointestinal Neoplasms in Wuwei City of Northwestern China From 1995 to 2016: A Hospital-Based Retrospective Observational Study - Liu, Kun; Song, Shuxuan; Fu, Ting; Liu, Yiwen; Zhang, Hui; Yan, Min; He, Zhen; Zhang, Weilu; Su, Haixia; Li, Zhao; Ji, Zhaohua; Shao, Zhongjun (Frontiers in Oncology, 2021)
Objective: To determine the inpatients’ characteristics and spatiotemporal distribution of major gastrointestinal (GI) neoplasms from 1995 to 2016 in Wuwei city, northwestern China. Method: Data from all paper and electronic medical records entered between 1995 and 2016 at 12 major public hospitals in Wuwei city, were retrospectively collected. Patients with GI neoplasms were identified and classified according to the International Classification of Diseases (ICD)-10. Trends in the incidence of major GI neoplasms were expressed as an annual percentage change (APC), and the Z test was used to assess the time fluctuation trends. Age-standardized incidence rates (ASIRs) were also calculated and the corresponding APC was estimated by Joinpoint software for long-term trend analysis. In addition, thematic maps of annual incidence at the township level were produced. Results: The results showed that among the 19,137 new inpatients identified with GI neoplasms in Wuwei, gastric cancer was the leading cause of morbidity, followed by cancers of the esophagus, colorectum, gastric cardia, liver, and pancreas with ASIRs of 21.8, 11.0, 6.3, 5.7, 4.4, and 1.7 per 100,000 person-years, respectively. Overall, there was a steady increase in the ASIR for all GI neoplasms, and male cases were 2.4 times more frequent than female cases. The ASIR significantly increased by 12.2% per year from 1995 to 2009 for all GI neoplasms, and the increase rates ranged from 9.2-16.9% per year for the individual GI neoplasm. Despite an increase by 1.4% per year from 2009 to 2016, the ASIR was decreased for esophageal, and gastric cardia caners by 4.6% and 17.3% per year, respectively. In addition, the annual incidence of all GI neoplasms showed significantly differential geographic distributions among different townships of the city during the study period.